PTC (Positive Temperature Coefficient) thermistor material with high breaking strength and preparation method thereof

By doping Ba6Ti17O40 cylindrical powder into PTC ceramic materials, the problem of PTC ceramic materials being easily fragile during the air pressure tightening process is solved, and PTC thermistor resistance material with high flexural strength and good voltage resistance is achieved, which significantly improves the safety of new energy vehicle heaters.

CN119638403APending Publication Date: 2025-03-18JIANGSU JUNCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411864145.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing PTC ceramic materials are prone to fragmentation during the air pressure tightening process, resulting in poor insulation and pressure resistance. Especially in the application of new energy vehicle heaters, due to high voltage and vibration, the debris will cause the heater to burn, which poses serious safety hazards.

Method used

The conventional high-pressure-resistant new energy vehicle PTC material composition using (Ba, Pb)TiO3+0.3atom%Nb2O5+1.0-5.0 weight sintering additive is used as the basic formula, and then the Ba6Ti17O40 cylinder powder is doped to improve the flexural strength of the material.

Benefits of technology

The high flexural strength (≥100MPa) of PTC thermistor material is achieved, while maintaining good voltage withstand strength and PTC characteristics, which significantly improves the safety and reliability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638403A_ABST
    Figure CN119638403A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a PTC (Positive Temperature Coefficient) thermistor material with high breaking strength. The preparation method comprises the following steps: preparing Ba6Ti17O40 cylindrical powder; and preparing high-breaking-strength PTC ceramic granulation powder, namely the PTC thermistor material, from the PTC ceramic powder and PTC ceramic basic powder together. The invention also discloses a high-strength PTC ceramic heating element prepared from the PTC thermistor material. According to the invention, Ba6Ti17O40 which is the same as a PTC main material is added into the material, the powder particles of the material are cylindrical, the corrosion of the material in a PTC body material is small during sintering, and even if a small amount of Ba6Ti17O40 is eroded, the performance of the PTC material does not generate large fluctuation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic piezoelectric materials, and in particular relates to a PTC thermistor ceramic material with high flexural strength and a preparation method thereof. Background Art

[0002] PTC ceramics generally refer to thermistor materials or components with a positive temperature coefficient of resistance. Typical PTC materials are semiconductor ceramic materials based on barium titanate, and their characteristics are that when the ambient temperature rises to a certain point (Curie point or switching temperature point), their resistance value will surge by several orders of magnitude. When this material is used as a heating element, its heating power hardly changes with the change of the applied voltage, so it has the function of automatic constant temperature. At the same time, it is widely used in industrial and military electronic equipment, as well as household appliances, because of its simple component structure, low cost, energy saving, no open flames, safety and reliability, and a series of advantages.

[0003] In the application field of heaters, PTC ceramics need to be processed into heaters through a series of processes such as pneumatic fastening (or extrusion) with electrode strips and aluminum tubes. However, PTC ceramics are naturally brittle and easily broken when fastened by pneumatic pressure. The debris sometimes pierces the insulating film and causes poor insulation withstand voltage. What is particularly serious is that the debris with electrodes will shorten the distance between the positive and negative electrodes, causing high-voltage burning. Especially in the application field of new energy vehicle heaters, due to the high operating voltage and the constant vibration environment, the debris will move and cause the heater to burn, posing a serious safety hazard.

[0004] For PTC components, the flexural strength needs to be >100MPa. The flexural strength of conventional PTC ceramics is around 50MPa. Therefore, researching and developing a PTC thermistor material with high flexural strength (>100MPa) so that it has a high flexural strength in addition to a series of basic properties of PTCR for new energy vehicles such as high withstand voltage strength is very necessary and urgent for the current explosive demand for new energy vehicles.

[0005] PTC is a polycrystalline ceramic material, and its fracture mode is usually along the grain boundary rather than transgranular fracture, because the grain boundary is a glass phase-rich area. The usual practice of strengthening ceramics is to add composite phases such as fibers and inorganic whiskers. However, for PTC ceramics, these composite phase addition methods often lead to deterioration of the electrical properties of the material, because the additives will produce a certain solid solution or chemical reaction with the ceramic body. Summary of the invention

[0006] The purpose of the present invention is to provide a PTC thermistor ceramic resistor material with good manufacturing performance, high voltage resistance and flexural strength (>100Mpa). The present invention adopts a conventional high-voltage (>550VDC / mm) PTC material composition for new energy vehicles of (Ba, Pb)TiO3+0.3atom%Nb2O5+1.0-5.0wt% sintering aid as the basic formula, and then doped with a material for increasing flexural strength to prepare a PTC thermistor ceramic resistor material with good performance, high voltage resistance and flexural strength.

[0007] To achieve the above technical objectives, the present invention discloses a method for preparing a PTC thermistor material with high flexural strength (>100MPa), comprising the following steps:

[0008] 1) Ba6Ti 17 O 40 Preparation of columnar powder: Ba6Ti 17 O 40 Nano whiskers, BaCO3, and TiO2 are mixed into raw materials in a weight ratio of (2.0-3.0):60:(65-75), put into a ball mill barrel, and zirconium oxide balls and deionized water are put into the ball mill to form a slurry. The weight ratio of the raw materials: zirconium oxide balls: water is 1:(1.5-2.5):(1.5-2.0); the ball milled slurry is dried and calcined in a muffle furnace to obtain columnar powder Ba6Ti 17 O 40 , and a columnar powder mixture thereof with BaTiO3 and TiO2, wherein Ba6Ti 17 O 40 The content of columnar powder is >90%;

[0009] 2) Take 100 parts of PTC ceramic base powder with a withstand voltage strength of >550 VDC / mm, add 0.03 to 5.0 parts of the columnar powder mixture, and prepare PTC ceramic granulated powder using a ceramic preparation process.

[0010] Preferably, the Ba6Ti 17 O 40 The diameter of the nanowhisker is 20 to 50 nm and the length is 50 to 200 nm.

[0011] Preferably, the ball milling in the ball mill in step 1) is performed in a planetary ball mill at 350 rpm for 2 to 4 hours.

[0012] Preferably, the slurry in step 1) is dried and then calcined in a muffle furnace at 1200-1350° C. for 6-20 hours.

[0013] Preferably, the columnar powder Ba6Ti obtained in step 1)17 O 40 The particle diameter is 0.5 to 2 μm and the length is 3 to 10 microns.

[0014] Preferably, the Tc temperature of the PTC ceramic base powder in step 2) is 120-250° C., and the average particle size of the powder is less than 5 μm.

[0015] Preferably, in step 2), 1.0 to 4.0 parts of the columnar powder mixture are added to every 100 parts of the PTC ceramic base powder. More preferably, in step 2), 2.0 to 3.0 parts of the columnar powder mixture are added to every 100 parts of the PTC ceramic base powder.

[0016] Preferably, the Ba / Ti ratio in the PTC ceramic granulated powder is 0.99 to 1.03.

[0017] The invention also discloses a PTC thermistor material with high flexural strength. The PTC thermistor material is prepared by the preparation method, and the flexural strength of the prepared PTC thermistor material is at least 100 MPa.

[0018] The present invention also discloses a high-strength PTC ceramic heating element. The PTC ceramic granulated powder prepared by the preparation method described above is dry-pressed into a ceramic green body, sintered according to a conventional sintering method for PTC ceramics, ground into a ceramic sheet, and metalized to obtain the high-strength PTC ceramic heating element.

[0019] Preferably, the ceramic body has a specification of 28.0×17.5×3.6 mm.

[0020] Preferably, the specifications of the ceramic optical sheet are 24×15×3.0 mm.

[0021] The present invention adds Ba6Ti, which is the same as the main material of PTC, to the material. 17 O 40 The powder particles of this material are columnar, and the dissolution in the PTC main material is small during sintering, even a small amount of Ba6Ti 17 O 40 Even if corroded, the performance of the PTC material will not fluctuate greatly. The pillars can exist across the grain boundaries, thus improving the flexural strength of the PTC material.

[0022] The advantages of the present invention are: 1. Nano Ba6Ti 17 O 40The whisker is the crystal nucleus, and BaO and TiO2 grow epitaxially along the crystal nucleus at high temperature to form a columnar object; ② The columnar object will continue to grow during the ceramic sintering process, and its length can eventually reach 10 to 30 microns, which is larger than the grain size of the ceramic (the average grain size of the ceramic is about 3.0 microns). Its existence can increase the flexural strength of the ceramic by 30 to 100% compared with before the improvement; ③ Ba6Ti 17 O 40 The addition of mixed powders did not significantly change its PTC properties, such as the material's withstand voltage strength, lift-to-resistance ratio, etc. There was no significant change before and after the improvement. This is because the Ba6Ti in the added powder 17 O 40 The material is the same as the ceramic body, and only the appropriate Ba / Ti ratio (0.99-1.03) needs to be maintained.

[0023] The present invention adds Ba6Ti, which is the same as the main material of PTC, to the material. 17 O 40 The powder particles of this material are columnar, and the dissolution in the PTC main material is small during sintering, even a small amount of Ba6Ti 17 O 40 The performance of the PTC thermistor ceramic resistor material of the present invention can achieve the following parameter requirements: Room temperature resistance: <10 4 Ω, lift-to-drag ratio: Rmax / Rmin>10 3 , resistance temperature coefficient α>6.0%, flexural strength ≥100MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 , Micrograph of the fracture surface of sample 185-BT30 of Example 1

[0025] Figure 2 , Example 1 Sample 185 series resistance-temperature characteristic comparison curve

[0026] Figure 3 , Micrograph of the fracture surface of sample 235-BT25 of Example 2 DETAILED DESCRIPTION

[0027] The content of the present invention is further described by the following embodiments. However, it should be noted that the following embodiments are only several examples that conform to the technical content of the present invention, and do not mean that the present invention is limited to the content described in the following embodiments.

[0028] The preparation method of the PTC thermistor material with a flexural strength of ≥100 MPa of the present invention comprises the following steps:

[0029] 1) Ba6Ti 17 O 40Preparation of columnar powder: Ba6Ti 17 O 40 Nano whiskers (diameter 20-50nm, length 50-200nm), BaCO3 (purity>99.7%), TiO2 (purity>99.9%) are used as raw materials, weighed according to the weight ratio of (2.0-3.0):60:(65-75), put into a nylon ball mill barrel, and zirconium oxide balls and deionized water are put into the barrel at the same time. The ratio of raw materials: zirconium oxide balls: water is 1:(1.5-2.5):(1.5-2.0) (weight), and the mixture is ball milled at 350 rpm in a planetary ball mill for 2-4 hours; after ball milling, the slurry is dried and calcined at 1200-1350°C in a muffle furnace for 6-20 hours to obtain columnar powder Ba6Ti with a diameter of 0.5-2μm and a length of 3-10 μm. 17 O 40 , and mixed powders with BaTiO3 and TiO2, among which Ba6Ti 17 O 40 The content of columnar powder is >90%;

[0030] 2) Take 100 parts of PTC ceramic base powder (Tc temperature 120-250°C, average powder particle size <5 microns) with a withstand voltage of >550VDC / mm, add 0.03-5.0 parts of the above-mentioned columnar powder mixture; use traditional ceramic preparation processes such as ball milling and granulation to obtain PTC ceramic granulated powder material with high flexural strength.

[0031] The above-mentioned PTC ceramic powder is dry-pressed into a ceramic body of 28.0×17.5×3.6 mm, sintered according to the conventional sintering method of PTC ceramics, and made into a 24×15×3.0 mm ceramic sheet after grinding. After metallization (upper electrode), a PTC ceramic heating element with high voltage resistance and high mechanical strength is obtained.

[0032] Embodiment 1:

[0033] In this example, Ba6Ti 17 O 40 The preparation of columnar powder is as follows: Ba6Ti 17 O 40 Nano whiskers (diameter 20-50nm, length 50-200nm), BaCO3 (purity>99.7%), TiO2 (purity>99.9%) are used as raw materials, weighed in a weight ratio of 2.2:59.5:78, put into a nylon ball mill barrel, and put into zirconium oxide balls and deionized water at the same time, the ratio of raw materials: balls: water is 1:2:1.5 (weight), and ball milled in a planetary ball mill at 350 rpm for 2.5 hours. After the slurry is dried, it is calcined at 1280℃ in a muffle furnace for 12 hours to obtain columnar particles with a diameter of 0.5-2μm and a length of 3-10 microns. 17 O40 , and mixed powders of BaTiO3 and TiO2, of which Ba6Ti 17 O 40 The content of columnar powder is about 92.0%.

[0034] Take 100 parts of the basic PTC ceramic formula (Tc = 185°C) with a withstand voltage strength of > 600 VDC / mm and add the above Ba6Ti 17 O 40 Mix 0 to 4.0 parts of powder, weigh the mass as shown in Table 1:

[0035] Table 1 Tc185 ingredients (unit: g)

[0036] Sample No. Tc185 basic formula powder <![CDATA[Ba6Ti 17 O 40 Mixed powder]]> 185-BT0 100 0 185-BT20 100 2.0 185-BT25 100 2.5 185-BT30 100 3.0 185-BT40 100 4.0

[0037] The above powder is processed by conventional ceramic preparation technology (ball milling, granulation, etc.) to obtain PTC ceramic granulated powder. Then, it is dry pressed into a ceramic body of 28.0×17.5×3.6 mm, sintered at 1310°C / 30 minutes according to the conventional sintering method of PTC ceramics, and then ground into a ceramic sheet of 24×15×3.0 mm. After metallization (upper electrode), a PTC ceramic heating element is obtained, and the ceramic element is subjected to resistance-temperature characteristic measurement, voltage withstand capability test, flexural strength test, etc.

[0038] Add Ba6Ti 17 O 40 Microstructure photo of the ceramic behind the column (185-BT30 sample) Figure 1 As shown. It can be seen that there are columns with a diameter of 2 to 4 μm and a length of about 20 μm in the figure. The fracture surface of the column is clearly visible, indicating that its fracture mode is transcrystalline fracture, which can significantly improve its fracture strength, which is clearly reflected in the value of flexural strength. The prepared material exhibits good PTC effect and mechanical properties; the resistance-temperature curve of the sample in Example 1 is as shown Figure 2 As shown by Figure 2 It can be seen that the doped samples all have excellent PTC characteristics, indicating that doping does not significantly affect their performance. However, the lift-to-resistance ratio decreases after doping, which will affect its electrical breakdown performance to a certain extent, especially when the doping amount is high. The specific performance parameters are shown in Table 2.

[0039] Table 2: Electrical and mechanical properties of 185 samples

[0040]

[0041] As can be seen from Example 1, adding Ba6Ti 17 O 40After the columnar material is added, the Curie temperature of the material does not change much, within the normal fluctuation range, but the lift-to-drag ratio and temperature coefficient change greatly, especially the voltage resistance strength of the material does not change much within the addition amount range of 2.0-3.0%, within the acceptable range. However, beyond this range, the voltage resistance drops significantly, and it is not a preferred material. In particular, the flexural strength of the improved material increases significantly, achieving the enhancement effect of the present invention.

[0042] Embodiment 2:

[0043] In this embodiment, Ba6Ti 17 O 40 The preparation of columnar powder is as follows: Ba6Ti 17 O 40 Nano whiskers (diameter 20-50nm, length 50-200nm), BaCO3 (purity>99.7%), TiO2 (purity>99.9%) are used as raw materials, weighed in a weight ratio of 2.5:59.5:82, put into a nylon ball mill barrel, and put into zirconia balls and deionized water at the same time. The ratio of raw materials: zirconia balls: water is 1:2:1.5 (weight), and ball milled in a planetary ball mill at 350 rpm for 2.5 hours. After the slurry is dried, it is calcined at 1280℃ in a muffle furnace for 12 hours to obtain columnar particles with a diameter of 0.5-2μm and a length of 3-10 microns. 17 O 40 , and mixed powders of BaTiO3 and TiO2, of which Ba6Ti 17 O 40 The content of the columnar powder is about 93.7%.

[0044] Take 100 parts of the basic PTC ceramic formula (Tc = 235°C) with a withstand voltage strength of >550VDC / mm and add the above Ba6Ti 17 O 40 Mix 0 to 5.0 parts of powder, weigh the mass as shown in Table 3:

[0045] Table 3 Tc235 ingredients (unit: g)

[0046] Sample No. Tc235 basic formula powder <![CDATA[Ba6Ti 17 O 40 Mixed Powder]]> 235-BT0 100 0 235-BT20 100 2.0 235-BT25 100 2.5 235-BT30 100 3.0 235-BT50 100 5.0

[0047] The above powder is processed by conventional ceramic preparation technology (ball milling, granulation, etc.) to obtain PTC ceramic granulated powder. Then, it is dry pressed into a 28.0×17.5×3.6mm ceramic body, sintered at 1285℃ / 20 minutes according to the conventional sintering method of PTC ceramics, and then ground into a 24×15×3.0mm ceramic sheet. After metallization (upper electrode), the PTC ceramic heating element is obtained, and the ceramic element is subjected to resistance-temperature characteristic measurement, voltage withstand capability test, flexural strength test, etc.

[0048] Example 2 Microstructure of ceramic after adding Ba6Ti17O40 columnar material (235-BT25 sample) Figure 3 As shown. It can be seen that there are columns with a diameter of 1 to 2 μm and a length of about 20 μm in the figure. The fracture surface of the column is clearly visible, indicating that its fracture mode is transgranular fracture, which can significantly improve its fracture strength, which is clearly reflected in the value of flexural strength. It is worth noting that the columns shown in this sample are smaller than those in the 185 series samples. The main reason is that the sintering temperature of this sample is low and the columnar growth is slow during the sintering process.

[0049] The material prepared in Example 2 exhibits good PTC effect and mechanical properties, and its performance parameters are shown in Table 4.

[0050] Table 4: Electrical and mechanical performance parameters of 235 series samples

[0051]

[0052] It can be seen from this embodiment that adding Ba6Ti 17 O 40 After the columnar material, the Curie temperature of Tc235 material does not change much at low content; but when the addition amount is higher than 3.0%, it drops significantly. Its withstand voltage strength changes within the low doping range and is also within the normal range, and the dopant has little effect on it. However, after the improvement, the flexural strength of the material is significantly increased, and the strengthening effect of the present invention is also achieved.

[0053] The PTC thermistor ceramic resistor material prepared by the present invention has good performance, high withstand voltage strength and high flexural strength, and adopts a conventional high withstand voltage (>550VDC / mm) PTC material composition for new energy vehicles of (Ba, Pb)TiO3+0.3atom%Nb2O5+1.0-5.0wt% sintering aid as the basic formula, and then doped with materials for increasing flexural strength. The performance of the PTC thermistor ceramic resistor material prepared by the present invention can achieve the following parameter requirements: Room temperature resistance: <10 4 Ω, lift-to-drag ratio: Rmax / Rmin>10 3 , resistance temperature coefficient α>6.0%, flexural strength ≥100MPa.

[0054] It should be understood that the terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two, but does not exclude the inclusion of at least one.

[0055] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0056] Finally, it should be noted that those skilled in the art can understand that in order to enable readers to better understand the present application, the embodiments of the present application provide many technical details. However, even without these technical details and various changes and modifications based on the above-mentioned embodiments, the technical solutions claimed for protection by the claims of the present application can be basically realized. Therefore, in practical applications, various changes can be made to the above-mentioned embodiments in form and detail without departing from the spirit and scope of the present application.

Claims

1. A method for preparing a PTC thermistor material with high flexural strength, characterized in that: The preparation method comprises the following steps: 1) Ba6Ti 17 O 40 Preparation of columnar powder: Ba6Ti 17 O 40 Nano whiskers, BaCO3, and TiO2 are mixed into raw materials in a weight ratio of (2.0-3.0):60:(65-75), put into a ball mill barrel, and zirconium oxide balls and deionized water are put into the ball mill to form a slurry. The weight ratio of the raw materials: zirconium oxide balls: water is 1:(1.5-2.5):(1.5-2.0); the ball milled slurry is dried and calcined in a muffle furnace to obtain columnar powder Ba6Ti 17 O 40 , and a columnar powder mixture thereof with BaTiO3 and TiO2, wherein Ba6Ti 17 O 40 The content of columnar powder is >90%; 2) taking 100 parts of PTC ceramic base powder with a withstand voltage strength of >550 VDC / mm, adding 0.03 to 5.0 parts of the columnar powder mixture, and preparing PTC ceramic granulated powder, i.e., the PTC ceramic granulated material with high flexural strength, by a ceramic preparation process; The flexural strength of the high flexural strength PTC ceramic granulated material is at least 100 MPa.

2. The method for preparing a PTC thermistor material with high flexural strength as claimed in claim 1, characterized in that: The Ba6Ti 17 O 40 The diameter of the nanowhisker is 20 to 50 nm and the length is 50 to 200 nm.

3. The method for preparing a PTC thermistor material with high flexural strength as claimed in claim 1, characterized in that: The ball milling in the ball mill in step 1) is performed in a planetary ball mill at 350 rpm for 2 to 4 hours.

4. The method for preparing a PTC thermistor material with high flexural strength as claimed in claim 1, characterized in that: The slurry in step 1) is dried and then calcined in a muffle furnace at 1200-1350° C. for 6-20 hours.

5. The method for preparing a PTC thermistor material with high flexural strength as claimed in claim 1, characterized in that: Ba6Ti columnar powder obtained in step 1) 17 O 40 The particle diameter is 0.5 to 2 μm and the length is 3 to 10 microns.

6. The method for preparing a PTC thermistor material with high flexural strength as claimed in claim 1, characterized in that: The Tc temperature of the PTC ceramic base powder in step 2) is 120-250° C., and the average particle size of the powder is less than 5 μm.

7. A PTC thermistor material with high flexural strength, characterized in that: The PTC thermistor material is prepared by the preparation method according to any one of claims 1 to 6, and the flexural strength of the prepared PTC thermistor material is at least 100 MPa.

8. A PTC ceramic heating element with high strength, characterized in that: The PTC ceramic granulated powder prepared by the preparation method described in any one of claims 1 to 6 is dry-pressed into a ceramic body, sintered according to the sintering method of PTC ceramics, ground into a ceramic sheet, and metalized to obtain the high-strength PTC ceramic heating element.

9. The PTC ceramic heating element according to claim 8, characterized in that: The ceramic body has a specification of 28.0×17.5×3.6 mm.

10. The PTC ceramic heating element according to claim 8, characterized in that: The specifications of the ceramic optical sheet are 24×15×3.0 mm.